1999
DOI: 10.1128/jvi.73.4.3169-3175.1999
|View full text |Cite
|
Sign up to set email alerts
|

Amphotropic Murine Leukemia Virus Entry Is Determined by Specific Combinations of Residues from Receptor Loops 2 and 4

Abstract: Pit2 is the human receptor for amphotropic murine leukemia virus (A-MuLV); the related human protein Pit1 does not support A-MuLV entry. Interestingly, chimeric proteins in which either the N-terminal or the C-terminal part of Pit2 was replaced by the Pit1 sequence all retained A-MuLV receptor function. A possible interpretation of these observations is that Pit1 harbors sequences which can specify A-MuLV receptor function when presented in a protein context other than Pit1, e.g., in Pit1-Pit2 hybrids. We reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The observation that no single point mutation in ELR1 completely abrogated gp90 binding suggests further that receptor binding to the viral envelope protein likely involves multiple contact points with residues within and outside of the CRD1 sequences. Thus, these data are consistent with other reports that multiple amino acid point mutations are required to completely eliminate receptor activity for FIV (11), avian sarcomaleukosis virus (16,17), human immunodeficiency virus (23), and murine leukemia virus (21).…”
Section: Discussionsupporting
confidence: 92%
“…The observation that no single point mutation in ELR1 completely abrogated gp90 binding suggests further that receptor binding to the viral envelope protein likely involves multiple contact points with residues within and outside of the CRD1 sequences. Thus, these data are consistent with other reports that multiple amino acid point mutations are required to completely eliminate receptor activity for FIV (11), avian sarcomaleukosis virus (16,17), human immunodeficiency virus (23), and murine leukemia virus (21).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the hypothesis that region A should be intracellular in PiT1 and extracellular in PiT2 seems in conflict with the observation that a PiT2 mutant with PiT1 region A sequence is receptor for both PiT1 and PiT2 cognate viruses [36] but shows unimpaired P i uptake function compared to PiT2 (P. Bøttger and L. Pedersen, unpublished work). Taken together the current data on receptor and transport functions of PiT1, PiT2, Pho4, and chimeras derived from these are all in favor [23,26,36,37,[45][46][47][48][49][50][51][52][53][54][55], or at least are not in conflict with [41], an extracellular position of region A. Thus, the most likely membrane topology of both PiT1 and PiT2 is that proposed by Salau¨n et al for PiT2 [23] (Fig.…”
supporting
confidence: 76%
“…Initial predictions of receptor topology were used to design a number of chimeras similar to those described here. Regions within those chimeras were identified that enhanced infection by GALV or amphotropic MLV respectively, and it was suggested that these regions were responsible for virus binding [ 30 - 33 ]. However, recent experiments have provided a new, experimentally verified topology for Pit2 [ 34 ], and several of the previously identified critical regions were found to lie on the inner surface of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%